Association Between the Albumin-Bilirubin (ALBI) Score and All-cause Mortality Risk in Intensive Care Unit Patients with Heart Failure - Jiuyi Wang; Kai Wang; Guibo Feng; Xin Tian (Global Heart)
Background: The albumin-bilirubin (ALBI) score has demonstrated prognostic value in a range for liver and heart diseases. However, its association with all-cause mortality in intensive care unit (ICU) patients with heart failure remains uncertain. Objective: This study sought to investigate the relationship between the ALBI score and the risk of all-cause mortality in ICU patients with heart failure. Methods and results: The ICU patients diagnosed with heart failure were selected from the Medical Information Mart for Intensive Care IV database (MIMIC-IV, version 2.2) and stratified into tertiles according to their ALBI scores. The primary outcome of interest was the occurrence of all-cause mortality within 365 days post-discharge. The analysis encompassed a cohort of 4,239 patients, with Kaplan-Meier curves indicating that individuals with higher ALBI levels exhibited an elevated risk of all-cause mortality (log-rank p < 0.001). Multivariate adjusted Cox regression and subgroup analysis demonstrated that individuals in T2 (hazard ratio (HR) 1.09, 95% CI 0.99–1.21) and T3 (HR 1.17, 95% CI 1.02–1.34) had an increased risk of mortality compared to individuals in T1 (p for trend < 0.001), and each incremental tertile in ALBI was linked to a 10% rise in mortality risk, while each individual unit increase in ALBI was associated with a 36% increase in mortality risk. This relationship was consistently observed across most subgroups, except for using or not using inotropes or vasopressors, different ages, different creatinine levels. The restricted cubic spline (RCS) analysis indicated a linear relationship between ALBI levels and the risk of all-cause mortality. Conclusion: The ALBI scores are independently associated with the risk of all-cause mortality in ICU patients with heart failure, particularly in those not using inotropes or vasopressors, younger patients, and with lower levels of creatinine. ALBI may help identify high-risk patients and optimize risk stratification in this population.